Design And Development Of Zigbee Based Wireless Remote Controlling And Data Acquisition Device Through Internet - Shibghatullah, Abdul Samad; M. Sultan, Sakhr; R. Abudulsheed, Hadeur; Fadilah, Suzi Iryanti; Abd Wahab, Mohd Helmy (Little Lion Scientific Islamabad Pakistan, 2014)
IrDa and Bluetooth have been used widely in many wireless monitoring and controlling devices. Although,these devices have been replaced the traditional wired systems and contribute in solving the high cost of such systems, there are drawbacks been emerged. The major disadvantages are the range limitation of Bluetooth module and the line of sight problem of IrDa device. A ZigBee is low cost and low power consumption wireless technology. It has a higher connectivity range than Bluetooth and doesn’t have line of sight problem. In this paper, an application model using ZigBee wireless remote controlling and data acquisition device as well as the use of internet connection to enable the device to be used worldwide is presented. Such system has several benefits such as portable, long wireless range, low power consumption, low cost and can be used worldwide using internet. The test results show its potential to be implemented in small offices and smart homes.